Influencia de la nicotinamida en la síntesis de ácidos grasos de novo en hígado graso: participación de la glucosa -6- fosfato deshidrogenasa - Ángeles Mejía, Selene (Universidad Autónoma Metropolitana, 2018)
The disruption of redox state homeostasis, the overexpression of lipogenic transcription factors and enzymes induced by the increase in the consumption of lipogenic precursors contained in sweetened beverages are determinants of the development of nonalcoholic fatty liver disease. This study evaluated the action of nicotinamide (NAM) on the expression of glucose-6- phosphate dehydrogenase (G6PD) and redox, oxidative, and inflammatory states in a model of nonalcoholic hepatic steatosis induced by high and chronic consumption of carbohydrates. Male rats were provided drinking water with 30% glucose or fructose ad libitum for 12 weeks. Additionally, 30 days after the beginning of carbohydrate administration, some rats were simultaneously provided with water containing 0.06% or 0.12% NAM for 5 h daily over the next 8 weeks. Biochemical profiles and expression levels of G6PD, tumor necrosis factor α (TNF α), and NADPH oxidase 4 (NOX4) were evaluated together with glutathione/glutathione disulfide (GSH/GSSG) and reduced nicotinamide adenine dinucleotide (phosphate)/nicotinamide adenine dinucleotide (phosphate) [NAD(P)H/NAD(P)] ratios and thiobarbituric acid reactive substances (TBARS). The results showed that hepatic steatosis induced by the chronic consumption of glucose or fructose was associated with body weight gain and increased levels of serum glucose, insulin, triacylglycerols, free fatty acids, transaminases, and TBARS. In the liver, the expression and activity of G6PD increased along with the GSSG, TBARS, and TG concentrations. These alterations were reduced by NAM treatment through the attenuation of increases in G6PD expression and activity and in the NADPH/NADP+ ratio, thereby slowing liver steatosis. NAM prevents redox, oxidative, and inflammatory alterations induced by high carbohydrate consumption.; El desajuste de la homeostasis del estado redox, la sobre-expresión de factores de transcripción de enzimas lipogénicas inducidos por el aumento del consumo de precursores lipogénicos contenidos en bebidas endulzadas son determinantes para el desarrollo del hígado graso no alcohólico. El presente estudio evalúa la acción de nicotinamida (NAM) sobre la actividad de glucosa-6-fosfato deshidrogenasa (G6PD) en un modelo experimental de esteatosis hepática no alcohólica inducida con glucosa ó fructosa al 30%. Ratas macho distribuidas en 6 grupos fueron sujetas a los siguientes tratamientos: 1) Control; 2) Glucosa; 3) Glucosa+NAM 0.06%; 4) Glucosa+NAM 0.12%; 5) Fructosa; 6) Fructosa+NAM 0.12%. Los carbohidratos fueron administrados en el agua de beber ad libitum por 12 semanas. El tratamiento de NAM inició 30 días posteriores a la administración de los carbohidratos por 5 horas durante las siguientes 8 semanas. Los parámetros evaluados fueron: perfil bioquímico, actividad, expresión y cantidad de G6PD, marcadores de estrés como glutatión reducido/glutatión oxidado (GSH/GSSG), dinucleotido de nicotinamida adenina (fosfato) reducido en relación a su respectiva forma oxidada [NAD(P)H/NAD(P)], sustancias reactivas al ácido tiobarbitúrico (TBARS). Así como, la concentración del factor de necrosis tumoral (TNF α), el mRNA de la NADPH oxidasa 4 (NOX4) y análisis histológico. Los resultados demostraron que el consumo crónico de glucosa ó fructosa provoca ganancia de peso corporal, aumento de glucosa, insulina, triacilgliceroles, ácidos grasos libres, transaminasas y TBARS en suero. A nivel hepático se incrementó actividad, expresión y cantidad de G6PD; así como las concentraciones de GSSG y TBARS junto con decremento de GSH/GSSG. Todas éstas alteraciones fueron prevenidas por NAM; a través de disminuir el aumento de la actividad de G6PD junto con NADPH/NADP+ y aumentar GSH/GSSG, disminuyendo la esteatosis hepática.